Hyrdeliv og paradisdrøm. Om Grundtvigs syn på hyrder - Mikkelsen, Inger Lise (Grundtvig-studier, 1994)
Pastoral Life and Paradise Dream By Inger Lise Mikkelsen In » The World Chronicle«, 1814, Grundtvig writes that the people of poetry, the ancient Hebrews, were a race of shepherds. The shepherds are not tied to material things, but live a life in freedom. On the plains, tending his flock, the shepherd experiences everything that is alive and growing as images of God’s creative power. Thus, he intuitively perceives his position as a creature facing his Creator.With this basic view as a point of departure, Grundtvig rewrites the Biblical stories of the shepherds Abraham and Jacob, Moses and David. They are all in an immediate, intimate contact with God, but as they live at different times, God endows them with different abilities appropriate for their concrete historical situation. Abraham and Jacob are the shepherds of faith, Moses is the shepherd of fight and hope, and David is the shepherd of love. They are all models, not because they are heroes, but because they recognize their own fragility.In the church texts, the shepherds of Christmas night play a particularly important role. In the hymn .The Christmas Chimes are sounding now. (Det kimer nu til julefest) from 1817, it is a main thought that the singers must remember pastoral life and come along into the field to hear the angel’s message together with the shepherds. To people who have a sense of the miraculous as the shepherds do, the field at Bethlehem is the centre of interest. Today only children possess a genuine shepherd’s mind. The adult can learn from them. The essential thing is to learn how to regain the child’s mind.In connection with the child theme, as shown by Chr. Thodberg, Grundtvig develops, through the 1820s, his understanding of baptism as the occasion when the adult may re-enter the dreamland of his childhood. Here Grundtvig uses Jacob’s ladder as an image of the adult’s return to his hitherto forgottem baptism.Another theme that Grundtvig makes frequent use of is the dilapidated cottage of the shepherd, his hut. He uses it as an image of man’s heart, which to Grundtvig is God’s dwelling on earth. The hut and the ladder become recurring images in Grundtvig’s hymns.Frequently the two images supplement each other so that the shepherds and Bethlehem may now move into the church. It is no longer the field, but the heart that rings with the angels’ song. Here, in the shepherd’s hut, is raised Jacob’s ladder, which reminds the singer of the childhood life under God’s care.In Grundtvig’s eyes every Christian is therefore a shepherd like the patriarchs. But above all the one baptized is like the good shepherd himself, renewing the paradise life that God created man for.